Recycling waste plastics in developing countries: Use of low-density polyethylene water sachets to form plastic bonded sand blocks. (October 2018) - Kumi-Larbi, Alexander; Yunana, Danladi; Kamsouloum, Pierre; Webster, Mike; Wilson, David C.; Cheeseman, Christopher
Highlights: LDPE is a problem in developing countries because of limited local recycling options. Simple and appropriate technology produces new materials from LDPE-bonded sand. Processing-property relationships for LDPE-bonded sand are reported. Community-driven waste management using this process has potential for global impact. Abstract: In many developing countries low-density polyethylene (LDPE) sheets, bags and water sachets are a major waste problem because local collection and recycling systems do not exist. As a result, LDPE has no value and is dumped causing aesthetic, environmental and public health issues. A relatively simple technology has been developed in the Cameroon that produces LDPE-bonded sand blocks and pavers. The application of this technology is an example of a community-driven waste management initiative that has potential to impact on the global plastics waste crisis because it can transform waste LDPE and other readily available types of plastics into a valuable local resource. In this research, waste LDPE water sachets have been melted and mixed with sand to form LDPE-bonded sand blocks. The effect of sand particle size and sand to plastic ratio on density, the compressive strength and water adsorption are reported. Optimum samples have been further characterised for flexural strength and thermal conductivity. LDPE-bonded sand is a strong, tough material with compressive strengths up to ∼27 MPa when produced under optimum processing conditions. The density and compressive strength increase as the particle size of the sand decreases. The potential for using this simple technology and the materials it produces to transform LDPE plastic waste management in developing countries is discussed.